Sea-ice, primary productivity and ocean temperatures at the Antarctic marginal zone during late Pleistocene. (15th August 2021) - Hartman, Julian D.; Sangiorgi, F.; Barcena, M.A.; Tateo, F.; Giglio, F.; Albertazzi, S.; Trincardi, F.; Bijl, P.K.; Langone, L.; Asioli, A.
Abstract: While Pleistocene glacial-interglacial cycles are commonly associated with strong waxing and waning of Northern Hemisphere ice sheets, the response of the Antarctic ice sheet and regional changes in oceanographic and environmental conditions to Pleistocene climate dynamics remain poorly constrained. We present a reconstruction of sea-ice cover, sea surface temperature and primary productivity off the Ross Sea margin (Adare Basin at the slope of the Drygalski Basin) during the marine isotope stages (MIS) 9 to 5 (350–70 thousands years ago, encompassing Terminations IV to II). Our multiproxy study relies on micropaleontology (diatoms, dinoflagellate cysts, benthic foraminifers), organic and inorganic geochemistry proxies (carbon and nitrogen isotopes, lipid biomarkers, XRF-data), and sedimentology (IRD) obtained from deep-sea core AS05-10. For each glacial-interglacial transition a clear succession of events can be observed: (near-)permanent sea ice cover during glacial stages is followed by ice-shelf break-up with episodic ice-free areas and surface water stratification. Notably, ice-shelf break-up precedes the increase in air temperature as measured in the Vostok ice core for each glacial-interglacial transition. Generally, air temperature over Vostok starts rising once sea-ice cover at site AS05-10 has significantly decreased, becoming seasonal, as indicated by the diatom species composition. This is also reflected by the high diatom productivity and increased water mixing at site AS05-10, which is indicative of its proximity to the Marginal Ice Zone. At the onset of Termination II (MIS6 to 5), high export productivity and dysoxic bottom water conditions occurred, while water temperature increased about 5 °C. During each interglacial spring/summer sea-ice cover is most reduced, and highest productivity occurs. Following each interglacial, the warm and cold fluctuations match the sawtooth character of the temperatures over Vostok. This record illustrates that at the Ross Sea margin, sea surface conditions and (export) productivity were strongly influenced by the natural climate variability of the Pleistocene. In light of this, current global warming may lead to increased ice-shelf break-up, water column stratification and shifts in the position/size of the Marginal Ice Zone with implications for algal species composition and diversity, and for primary productivity. Highlights: Late Pleistocene glacial-interglacial transitions offshore the Ross Sea show a clear succession of events. Glacial stages are near permanently sea ice cover and are followed by ice-shelf break up and water stratification. Ice-shelf break up seems to precede air temperature rise as measured in the Vostok ice core. At MIS6 to 5 Termination, productivity increases while ocean temperatures rise by 5 °C. On-going global warming may shift the position/size of the Marginal Ice Zone with implications for primary productivity.